ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN DARING DI SMK SE-KECAMATAN KAYUAGUNG - Juai Aptriyana; Neta Dian Lestari; Januardi Januardi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2021)
The problem in this research is how the learning difficulties of students in online learning at SMKs in the Kayuagung District are for the 2020/2021 academic year. The purpose of this study was to determine the learning difficulties of students in online learning at SMK in Kayuagung District. The method used in this study is a qualitative descriptive method.The results showed that the average answer of 99 respondents/students from positive negative questionnaire statements was 72.29% with the category "Enough Difficulty" meaning that when online learning students had difficulties with technical obstacles that affected the signal so that there was a lack of reciprocal interaction between students. and teachers, students also have difficulty understanding the material presented by the teacher during online learning activities and delayed responses due to signals that interfere with student-teacher communication. From the results of this study, it is expected that teachers and schools can pay attention to the constraints experienced by students, for example signal constraints that make students late in collecting assignments and absent to provide time slack for students during online learning and is expected to be an evaluation material for the future.Â Keywords : Learning Difficulties, Online Learning